Pelatihan Grounding dan Mindfulness untuk Menurunkan Stres dan Meningkatkan Kualitas Tidur Mahasiswa Kebidanan - Nonik Ayu Wantini; Ian Rossalia Pradita Puteri; Fx. Joko Krisdiyanto; Eko Mindarsih; Suwarsi Suwarsi (LPPM Universitas Pendidikan Mandalika (UNDIKMA), 2026)
This community service program aims to enhance midwifery students’ ability to manage stress and improve sleep quality through training in grounding and mindfulness techniques. The program involved educational sessions, skills training, and guided independent practice of grounding and mindfulness over a 28-day period. Participants consisted of 27 undergraduate midwifery students in semesters 2, 4, and 6 at Universitas Respati Yogyakarta. Evaluation was conducted by measuring stress levels using the Perceived Stress Scale (PSS) and sleep quality using the Pittsburgh Sleep Quality Index (PSQI) before and after the intervention. The results showed a reduction in the median stress score from 18 to 15, along with an improvement in sleep quality indicated by a decrease in the median PSQI score from 11 to 6. Wilcoxon test analysis revealed statistically significant differences in both stress levels (p = 0.002) and sleep quality (p = 0.000) following the grounding and mindfulness training. It can be concluded that grounding and mindfulness training is effective as a non-pharmacological strategy to reduce stress levels and improve sleep quality among university students.